(untitled) (Research, Society and Development, 2020)
Hemoglobins are macromolecules responsible for the process of gas exchange in the human organism. Hemoglobinopathies are diseases of hemoglobins that happen due to mutational processes in the globin chains. Sickle cell anemia is the most prevalent genetic disease in the world. In Brazil, the incidence and prevalence of the disease is considered a public health problem, with northeast Brazil being the most prevalent region. Still unknown by most of the population and health professionals, health education has its process of knowledge dissemination. Considering these facts, the present study aimed to identify effective playful interventions in this practice, with a view to subsidizing reflection and improvement of teaching in this area. The elaboration of chess games, checkers, tic-tac-toe and puzzle composed with elements inherent to this hemoglobinopathy, provides students of pharmacy at the State University of Paraíba, Campina Grande campus, the playful contact in the learning of this pathology, providing cognitive stimulation in the teaching / learning process. Due to the good results obtained, it is intended to use the games in school lectures and in the process of education of agents and health professionals.